Kajian Musthalah Kitab Nuzhat an-Nazhar Fi Taudih Nukhbat al-Fikar di Ma’had Darul Hadis Khadimus Sunnah Bandung - Ahmad Rif’at Al-Farizi (Jurnal Riset Agama, 2022)
This paper examines the book of Musthalah al-Hadith, the book of Nuzhat an-Nazhar Fi Taudih Nukhbat al-Fikar which was studied in Ma'had Darul Hadith Khadimus Sunnah Bandung. This paper aims to introduce the book of turots in the field of hadith science or Musthalahat al-Hadith with the object of the book Nuzhat an-Nazhar Fi Taudih Nukhbat al-Fikar by al-Hafidz Ibn Hajar al-Asqalani. And know how the methods used by the Institute of Ma'had Darul Hadith Khadimus Sunnah in studying and teaching the book of Nuzhat an-Nazhar and how to implement it. Using derifrifyive research methods, this study proves that the book of Nuzhat an-Nazhar is a systematic book of Musthalah al-Hadith and uses its own manhaj in the arrangement of its chapters. So that the book is used as a backrest or reference of scholars afterwards in compiling books in the field of hadith science and becomes the first gate for hadith students in studying hadith science. The methods used by Ma'had Darul Hadith Khadimus Sunnah in studying the book are the Nazhari and Tathbiqi methods in the form of Talaqi, Mulazamah and Munaqasyah. In its implementation, the students are able to understand the materials studied and can analyze the hadith of both sanad and matan analysis as evidenced in the final task that is in the form of takhrij hadith.